Report on mining development plan of Iscaycruz (Oyon) area: report of metallurgical investigation - Japan International Cooperation Agency (1986)
Regarding the "Mine Development Survey Works at the Area of ISCAYCRUZ of the Republic of Peru" promoted by the Metal Mining Agency of Japan as one of its projects for the fiscal year of 1985, a series of various mill tests in laboratorial scale for the samples from the ore deposits of ISCAYCRUZ have been carried out. The results of the tests are summarized and reported herewith.